Pengaruh Digitalisasi Dan Persepsi Terhadap Kualitas Pelayanan Administrasi Kependudukan Di Kelurahan Mangga Besar Tahun 2021 - Irma Rahayua; Dodi Rahmat Setiawan; Mohammad Sofyan (Jurnal Ilmu Administrasi Publik, 2021)
The purpose of this study was to analyze the effect of digitalization and perception  on  the  quality  of  population  administration  service  in Mangga Besar Village, 2021. The theories used in this study were the theory by Soemantri on digitalization, Sondang P Siagian on incentives and Zeithaml, Parasuraman & Berry in Lupiyoadi on service quality. The method used in this study was a quantitative method through the distribution of questionnaires with a total population of 73 respondents and the sample was also 73 by using Random Sampling and Saturated Samples, all populations were used as samples. Based on the results of the study using partial and multiple linear regression analysis with the help of SPSS version 24 for windows, it showed that the partial t test results indicated that digitalization has a positive and significant effect on service quality by 7.6%, and perception affects service quality by 84.8%. The results of the F test show that simultaneously digitization and perception variables have a significant effect on service quality with a  value  of  41.64%.  The  influence  of  the  Adjusted  Square  (R2) Coefficient of Determination Value was 0.849 or 84.9% because Fcount was greater than Ftable and the rest of 7.49% is affected by other factors not studied (epsilon) in Mangga BesarVillage. The purpose of this study was to analyze the effect of digitalization and perception  on  the  quality  of  population  administration  service  in Mangga Besar Village, 2021. The theories used in this study were the theory by Soemantri on digitalization, Sondang P Siagian on incentives and Zeithaml, Parasuraman & Berry in Lupiyoadi on service quality. The method used in this study was a quantitative method through the distribution of questionnaires with a total population of 73 respondents and the sample was also 73 by using Random Sampling and Saturated Samples, all populations were used as samples. Based on the results of the study using partial and multiple linear regression analysis with the help of SPSS version 24 for windows, it showed that the partial t test results indicated that digitalization has a positive and significant effect on service quality by 7.6%, and perception affects service quality by84.8%. The results of the F test show that simultaneously digitization and perception variables have a significant effect on service quality with a  value  of  41.64%.  The  influence  of  the  Adjusted  Square  (R2) Coefficient of Determination Value was 0.849 or 84.9% because Fcount was greater than Ftable and the rest of 7.49% is affected by other factors not studied (epsilon) in Mangga BesarVillage.